The Effect of Radiation Defects in a Metal Target on the Error in the Thermal-Imaging Diagnostics of Powerful Ion Beam; Instruments and Experimental Techniques; Vol. 62, No. 2 - Egorova Yu. I. Yulia Ivanovna; Prima A. I. Artem Igorevich; Zhu X. Xiaopeng; Ding L.; Pushkarev A. I. Aleksandr Ivanovich; Lei M. K. Ming Kai (2019, 2019)
Title screen